2020
DOI: 10.1038/s41598-020-63475-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut metagenomic and short chain fatty acids signature in hypertension: a cross-sectional study

Abstract: Hypertension is an independent and preventable risk factor for the development of cardiovascular diseases, however, little is known about the impact of gut microbiota composition in its development. We carried out comprehensive gut microbiota analysis and targeted metabolomics in a cross-sectional study of 29 non-treated hypertensive (HT) and 32 normotensive (NT) subjects. We determined fecal microbiota composition by 16S rRNA gene sequencing and bacterial functions by metagenomic analysis. The microbial metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 66 publications
12
115
0
1
Order By: Relevance
“…SCFAs, including acetate, propionate, and butyrate, are produced by specific gut microbes by fermentation of otherwise indigestible dietary fibers [ 46 ]. Fecal and plasma levels of SCFA are associated with the abundance of SCFA-producing microbiota in the gut and the intake of dietary fibers [ 36 , 47 , 48 ]. Butyrate-producing microbiota include bacteria from the families Ruminococcaceae and Lachnospiraceae , but also bacteria such as Anaerobutyricum hallii and Anaerostipes spp.…”
Section: Gut Microbiota In Hypertensionmentioning
confidence: 99%
“…SCFAs, including acetate, propionate, and butyrate, are produced by specific gut microbes by fermentation of otherwise indigestible dietary fibers [ 46 ]. Fecal and plasma levels of SCFA are associated with the abundance of SCFA-producing microbiota in the gut and the intake of dietary fibers [ 36 , 47 , 48 ]. Butyrate-producing microbiota include bacteria from the families Ruminococcaceae and Lachnospiraceae , but also bacteria such as Anaerobutyricum hallii and Anaerostipes spp.…”
Section: Gut Microbiota In Hypertensionmentioning
confidence: 99%
“…A number of studies have shown that PC consumption induces changes in SCFA levels produced by gut microbiota [99], mainly acetate, propionate, and butyrate. Grapefruit PCs have been demonstrated to raise SCFAs in rats [100], while PCs of red wine and black tea reduced them [101].…”
Section: Effects Of Olive Oil Phenolic Compounds On Lipid Metabolismmentioning
confidence: 99%
“…These species are positively correlated with systolic and diastolic BP. The same study reported that the level of ScFAs in the plasma was low, whereas the level of fecal SCFAs was significantly higher, indicating that the intestinal ScFA absorption rate is low (58). The ScFA content is positively correlated with Clostridium, Lactobacillus and Blautia XlVa levels, whereas acetic acid, propionic acid and butyric acid levels are inversely proportional to the abundance of Streptococci, Enterococci and other bacteria (22).…”
Section: Crosstalk Between Gut Microbiota and Scfas And Modulation Omentioning
confidence: 91%
“…According to the data released in 2015 relating to medical office BP measurements, hypertension has a global prevalence of 1.13 billion and 150 million cases in central and Eastern Europe, respectively. In recent years, studies (58) have found that dysbiosis of the intestinal flora affects BP stability. Metabolites from microbial flora, such as SCFAs and TMAO, are implicated in the pathogenesis of cVd.…”
Section: Crosstalk Between Gut Microbiota and Scfas And Modulation Omentioning
confidence: 99%
See 1 more Smart Citation